Fruit peel waste: characterization and its potential uses - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2017)
Globally, India is the leading producer of fruits. Fruits after consumption leave a peel which is a nuisance to the environment as a solid waste. In this article, commonly available large volume-fruit peels (FP) (viz. banana, orange, citrus, lemon and jackfruit) were investigated for surface, physical and chemical characteristics with a view to propose their valorization in detail. Each FP was characterized by proximate and ultimate analysis, porosity, particle density, bulk density, point of zero charge (pH(pzc)), surface pH, surface charges, water absorption capacity, BET surface area, scanning electron microscopy, Fourier transform infrared spectroscopy and TGA/derivative of thermogravimetric. The BET surface area of FP is very less, between 0.60 and 1.2 m(2)/g. The pH(pzc) and surface pH values of orange peel (OP), citrus peel (CP), lemon peel (LP) and jackfruit peels (JFP) are in the range of 3-4. The pH(pzc) value and surface pH of banana peel (BP) is closer to 7. The order of surface acidity is OP > LP > CP > JFP > BP. From TG curves it is clear that FPs are stable below 150 degrees C. The results will be useful for rational design, when FP is used as a substrate for bioactive compounds, phenolic antioxidants, organic acids, enzymes, biofertilizer, production of energy and as adsorbents.